Perineuronal Net Receptor PTPσ Regulates Retention of Memories - Lesnikova, Angelina; Casarotto, Plinio; Moliner, Rafael; Fred, Senem Merve; Biojone, Caroline; Castrén, Eero (Frontiers in Synaptic Neuroscience, 2021)
Perineuronal nets (PNNs) have an important physiological role in retention of learning by restricting cognitive flexibility. Their deposition peaks after developmental periods of intensive learning, usually in late childhood, and they help in long-term preservation of new acquired skills and information. Modulation of PNN function by various techniques enhances plasticity and regulates retention of memories, which may be beneficial when memory persistence entails negative symptoms such as post-traumatic stress disorder (PTSD). In this study, we investigated the role of PTPσ (receptor-type tyrosine-protein phosphatase S, a phosphatase that is activated by binding of chondroitin sulfate proteoglycans from PNNs) in retention of memories using Novel Object Recognition and Fear Conditioning rodent models. We observed that mice haploinsufficient for PTPRS gene (PTPσ+/-), although having improved short-term object recognition memory, display impaired long-term memory in both Novel Object Recognition and Fear Conditioning paradigm, as compared to WT littermates. However, PTPσ+/- mice didn't show any differences in behavioral tests that do not heavily rely on cognitive flexibility, such as elevated plus maze, open field, marble burying and forced swimming test. Since PTPσ has been shown to interact with and dephosphorylate TRKB, we investigated activation of this receptor and its downstream pathways in limbic areas known to be associated with memory. We found that phosphorylation of TRKB and PLCγ are increased in the hippocampus, prefrontal cortex and amygdala of PTPσ+/- mice, but other TRKB-mediated signaling pathways are not affected. Our data suggest that PTPσ downregulation promotes TRKB phosphorylation in different brain areas, improves short-term memory performance but disrupts long-term memory retention in the tested animal models. Inhibition of PTPσ or disruption of PNN-PTPσ-TRKB complex might be a potential target for disorders where negative modulation of the acquired memories can be beneficial.